Villa Mairea. El racionalismo nórdico de Alvar Aalto - Godoy Vera, Giuliana María (2015)
This analysis addresses one of the most representative works of modern single house: Villa Mairea from the nordic architect Alvar Aalto. This work is an excellent example of a modernity that seeks local roots and is not intended to be part of an international style, despite the international recognition of the work and its author. Work of space, materiality, and adaptation to a specific climate and location are analyzed. The three parts of the article seek to guide the reading among the most important variables of the work, concluding with its importance as a transcendent work of mid-twentieth century, but to this day projection.